2014
DOI: 10.1016/j.neuroimage.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Automated longitudinal intra-subject analysis (ALISA) for diffusion MRI tractography

Abstract: Fiber tractography (FT), which aims to reconstruct the three-dimensional trajectories of white matter (WM) fibers non-invasively, is one of the most popular approaches for analyzing diffusion tensor imaging (DTI) data given its high inter-and intra-rater reliability and scan-rescan reproducibility. The major disadvantage of manual FT segmentations, unfortunately, is that placing regions-of-interest for tract selection can be very labor-intensive and time-consuming. Although there are several methods that can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…An isotropic 1.5 × 1.5 × 1.5 mm 3 seeding grid was used for all datasets. From these whole-brain tractography results, several fiber bundles were segmented: the arcuate fasciculus (AF), as described in Catani and Thiebaut de Schotten (2008);the corticospinal tracts (CSTs) that terminate in the primary motor cortex (M1) were segmented as described in Wakana et al (2007) and Aarnink et al (2014). The ROIs selecting M1 were 26 mm superior to the corpus callosum on the mid-sagittal slice;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An isotropic 1.5 × 1.5 × 1.5 mm 3 seeding grid was used for all datasets. From these whole-brain tractography results, several fiber bundles were segmented: the arcuate fasciculus (AF), as described in Catani and Thiebaut de Schotten (2008);the corticospinal tracts (CSTs) that terminate in the primary motor cortex (M1) were segmented as described in Wakana et al (2007) and Aarnink et al (2014). The ROIs selecting M1 were 26 mm superior to the corpus callosum on the mid-sagittal slice;…”
Section: Methodsmentioning
confidence: 99%
“…the corticospinal tracts (CSTs) that terminate in the primary motor cortex (M1) were segmented as described in Wakana et al (2007) and Aarnink et al (2014). The ROIs selecting M1 were 26 mm superior to the corpus callosum on the mid-sagittal slice;…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach has been applied to diffusion-weighted (DW) MRI and combined with tensor-based registration to align images within and across subjects for region-of-interest (ROI) analyses of diffusion measures (Keihaninejad et al, 2013). This approach can also be used to transfer ROIs from an atlas with the purpose of labeling tractography streamlines (Aarnink et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies [8, 9, 13, 1419] have already investigated the effects of multiple software suites on a single dataset, finding that one often outperforms another in a certain regard. For instance, the FreeSurfer suite [20] is widely used for cortical and subcortical parcellation, yet recent studies have shown that Advanced Normalization Tools (ANTs) [21], a more recently developed suite of software, outperforms FreeSurfer in certain aspects [17, 18, 22].…”
Section: Introductionmentioning
confidence: 99%